Penguatan Nilai-nilai Tasawuf Pada Fenomena Hijrah Di Zaman Millenial - Zakiyah (Prodi Ilmu al-Qur'an dan Tafsir, 2019)
This article questions the shifting and development of the meaning of migration in millennial times, especially what happens to urban Muslim communities. This study aims to determine the meaning of hijrah from the behaviors and amaliyah of ubudiyah that arise. And things that influence and background the emergence of a shift in meaning. For data collection, this writing uses library research (libary reseach), and phenomenology methods that try to explain or reveal the meaning of a concept or phenomenon of experience based on awareness that occurs in some individuals. The results of this study concluded that what caused the shift and development of the meaning of hijrah was motivated by several factors. First, there is freedom of expression in religion. Second, the development of the era is increasingly advanced. Third, there is an effort to capitalize on religious concepts, including the concept of hijrah.